Functional annotation of the nodule transcriptome of the actinorhizal hosts Datisca glomerata and Ceanothus thyrsiflorus. - Marco Guedes Salgado (Stockholm University, 2018)
The nodule transcriptome of Datisca glomerata was de novo assembled by Trinity and annotated using the Trinotate pipeline. Transcript abundance was estimated by RSEM and presented as transcript per million reads (TPM) for five independent samples.
Keywords: Computational Biology; 60705 Plant Physiology; Biological Sciences; Biologi; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)